(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The understanding of the most important aspects of Kazakhstani musical culture such as «national and international», «traditions and innovations», the use of national musical matter are shown in the article through publicistic heritage of E. Rakhmadiev. Special attention was paid to the analysis of E. Rakhmadiev’s statements on appearance and development of Kazakh symphonism in historical contect, its cultural value and recommendations for its further development. The facts on culture and aesthetics as far as analysis of Rakhmadiev’s statements allow to reveal features of creation of «symphonic kuy» genre and its implementation in composers’ activities. Key words: musical culture of Kazakhstan, Kazakh music, tradition and innovation, national art, symphonic kui.